PENGARUH PEMANFAATAN PERPUSTAKAAN SEKOLAH TERHADAP PRESTASI BELAJAR PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 1 AMBAWANG - Marthilda, Fera; Aminuyati, Aminuyati; Achmadi, Achmadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research is to know the influence of school library utilization towards the student’s learning achievement of the economic subject on class XI IPS in SMAN 1 Ambawang. The method in this research is the associative method. This is a descriptive research. The population in this research is 134 students. The number of samples in this research is 57 students. Data collection techniques in this research are direct communication techniques, indirect communication techniques (library utilization questionnaire), and documentary techniques (data of student’s learning achievement). The result of this research showed that there is the positive influence of library utilization towards the student’s learning achievement on the economic subject in SMAN 1 Ambawang. This can be known from the t value is 13,072 which shows there is influence of library utilization towards student’s learning achievement. When it compared with t table on the significance level of 0,05 of 0,867 so that Ha is accepted. The conclusion of this research is library utilization has a significant effect on the student’s learning achievement of economic subject in SMAN 1 Ambawang. Keywords: Library Utilization, Learning Achievement, Economic Subject